Validation of the self-compassion scale in a sample of Italian special needs teacher - Ragni, Benedetta; Sulla, Francesco; Toto, Giusi Antonia; Limone, Pierpaolo (Frontiers in Psychology, 2023)
Introduction Special needs teachers deliver crucial care to their students by showing a particular attitude toward them. However, they usually face stressful situations that negatively impact their capacity to support their students, often reporting higher levels of burnout compared to teachers from mainstream education. Self-compassion has been seen to function as a protective factor against teacher stress, enhancing their resilience and coping abilities. Methods The current study aimed to evaluate the factorial structure, reliability, and validity of the Self-compassion Scale (SCS) in a sample of Italian special needs teachers (R1). In addition, it was investigated whether the satisfactory internal reliability of the SCS is confirmed (R2). Finally, the validity of the SCS criterion was assessed, assuming that each of its subscales would be related to anxiety, measured with GAD-7, and with resilience, measured with the BRS (R3). A sample of 629 teachers was enrolled in this study and completed an online questionnaire. Results Overall, the confirmatory factor analysis showed good or acceptable indices of fit to the data supporting the use of SCS to measure self-compassion in Italian special needs teachers. Discussion The tool could be helpful for future research to start exploring the self-compassion dimension at school as a protective factor that may foster teachers’ and, consequently, students’ well-being.